Potential for material valorization of composites (glass fiber in polyester resin) in concrete: performance evaluation on mortar - Zambon, Agnès; Deleglise-Lagardere, Mylène (Frontiers in Materials, 2024)
Glass fibers with polyester resin structural composites are highly attractive in many sectors such as transportation industries thanks to their low density and fairly good mechanical properties. However, their end-of life management is not yet satisfactory. Composites mostly end in energy recovery in the best-case scenario or, worse, in landfill. Transformation into shreds and powders for reuse as a new source of raw material for the construction sector (concrete) is an economically and environmentally attractive recovery solution. The present study investigates the development of a concrete filled with glass/polyester composite shreds. To this end, rheological (cone spread) and physico-mechanical (density and mechanical strength in flexion and compression) characterisation tests were carried out. Several mix design were tested in order to understand the impact of introducing composite shreds as a substitute for sand. Composite shreds were introduced in the following ratios by volume: 0 ; 1 ; 1.5 ; 2 ; 2.5 ; 3 and 7% with water and cement ratio equal to 0.5 ; 0.6 and 0.7.The results obtained show that workability decreases with the substitution of sand by shreds. For a substitution of sand by shreds of 2%, it is relatively small and the pouring of the mortar is still feasible. The decrease can be attributed to the water absorption of the composite shreds. Concerning mechanical results, for formulations with a substitution percentage of composite shreds lower than 3%, mechanical strength (both compression test and flexure test) are slightly higher than the reference sample. The increase of compressive strength which can be observed is at its maximum equal to 10% compared to the reference sample. These results are in line with density results which are also slightly higher than the reference sample. This effect can be attributed to water absorption of composite shreds and to the filling effect of the powders. For 7% of substitution, mechanical strength is lower than the reference (30%) with a compressive strength equal to 33MPa (47MPa for reference). For 7% of substitution, a decrease in density is also observed (6%) and can be explained by the porosity created by the incorporation of the shreds.